The Urgency of Teaching Future Essential Skills to Mathematics and Science Education Students to Enhance the Quality of Teaching in the Modern Education Era - Yanti, Fitri April; Wardana, Rendy Wikrama; Binti Abdul Rahim, Suzieleez Syrene; Sathasivam, Renuka V.; Thohir, M. Anas; Heryensi, Elza; Sartika, Rita (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This research aims to explore the important skills that mathematics and science education students must possess to enhance the quality of teaching in the modern education era. This study uses a qualitative approach with a systematic literature review method. The focus of the study is on annual publication trends, research methods, and skills emphasized in mathematics and science education, from the Scopus database during the 2015-2024 period. A total of 50 papers were analyzed to present ideas, findings, and knowledge literature with an academic focus. This data analysis was conducted using thematic analysis, namely research focused on exploring how essential skills are implemented or integrated in mathematics and science education. The results of the research show that the peak of the research trend on important future skills for mathematics and science students will be in 2023 and will still be ongoing in 2024. The methods most frequently used in the last 15-year research period are quantitative, followed by non-empirical, qualitative, mixed, and research and development. Future skills such as critical thinking, creative thinking, problem solving, collaboration, and communication are very important to teach prospective teachers in improving the quality of teaching. This study also revealed that STEM learning is most widely used to teach future skills. In the future, this research can become a reference or point of reference in preparing the skills that must be taught to prospective teachers today for quality education in the future with the role of professional teachers.